H HUBUNGAN KOMUNIKASI EFEKTIF TERHADAP KECEMASAN PASIEN DENGAN PEMASANGAN KATETER DI IGD - Huzaifah, Zaqyyah; Iswara, Widya (LPPM Universitas Sari Mulia, 2023)
Background: Anxiety is a reaction that can be experienced by anyone, which if excessive anxiety will cause interference and hinder a person's function in life. Anxiety arises when there is a lack of communication between patients and nurses because the spearhead of health is the nurse. nurses must have good communication with patients in order to provide understanding to patients about their illness. Objective: This study aims to determine the relationship of effective communication to patient anxiety with catheter insertion in the emergency room. Methods: This study used correlative analytics. The population was patients with catheter insertion and the sample amounted to 48 people. Sampling with purposive sampling. Results: The statistical test results obtained p value (0.001) < α (0.05) so it can be concluded that there is a relationship between effective communication and patient anxiety with catheter insertion in the emergency room. Conclusion: Nurses must have the ability to carry out effective communication so as to reduce patient anxiety in the emergency room.